2009
DOI: 10.3164/jcbn.08-269
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for the Development or Regression of Fatty Liver in Japanese Adults

Abstract: Fatty liver is commonly associated with alcohol or metabolic syndrome. We aimed to examine the longitudinal aspects of fatty liver, and clarify the independent predictors for the development or regression of fatty liver. In the present study, the clinical features of 1578 Japanese adults (1208 men and 370 women; 35 to 69 years of age) who visited our center both in 2000 and 2007–2008 were recorded and compared, including liver status diagnosed by ultrasonography. Of the 1578 participants, 217 (13.8%) showed fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
4
19
1
Order By: Relevance
“…Similar findings were reported in another study; where elevated total cholesterol level, triglycerides and LDL, and decreased HDL were significantly associated with higher degree of fatty liver, but only total cholesterol and triglycerides were the independent predictors [18]. Also, high total cholesterol and triglycerides were associated with the development of NAFLD [22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings were reported in another study; where elevated total cholesterol level, triglycerides and LDL, and decreased HDL were significantly associated with higher degree of fatty liver, but only total cholesterol and triglycerides were the independent predictors [18]. Also, high total cholesterol and triglycerides were associated with the development of NAFLD [22].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly findings were reported by other studies [18,19,20,21]. Contrary to that, other studies concluded that age was a non-significant predictor for fatty liver [22,23]. The discrepancy of age association with high prevalence of NAFLD as well as its complications may be attributed to the duration of disease rather than age.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Of 3,296 abstracts identified from initial search and 13 additional studies from scanning the results section of cohort studies focusing on other risk factors of NAFLD, 27 potentially relevant publications were retrieved for detailed assessment (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text evaluation, six articles were further excluded, including four studies for no usable data , and two for lack of adjusted risk estimates . Therefore, 21 cohort studies were included in the meta‐analysis . There were a total of 381,655 participants in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%